2017
DOI: 10.1002/ajmg.a.38083
|View full text |Cite
|
Sign up to set email alerts
|

TSC2 c.1864C>T variant associated with mild cases of tuberous sclerosis complex

Abstract: Tuberous sclerosis complex (TSC) is an autosomal dominantly inherited disorder with variable expressivity associated with hamartomatous tumors, abnormalities of the skin, and neurologic problems including seizures, intellectual disability, and autism. TSC is caused by pathogenic variants in either TSC1 or TSC2. In general, TSC2 pathogenic variants are associated with a more severe phenotype than TSC1 pathogenic variants. Here, we report a pathogenic TSC2 variant, c.1864C>T, p.(Arg622Trp), associated with a mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
(19 reference statements)
1
11
0
Order By: Relevance
“…Our findings were also consistent with those of previous studies that determined Arg622Trp 24 and Arg1200Trp 23 TSC2 pathogenic missense variants to be associated with a milder phenotype. Although the sample size of three was too small for statistical analysis, two of the children (Arg622Trp and Arg1200Trp) had composite scores in the “average” range, whereas the third (Arg1200Trp) had a “very high” composite score.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings were also consistent with those of previous studies that determined Arg622Trp 24 and Arg1200Trp 23 TSC2 pathogenic missense variants to be associated with a milder phenotype. Although the sample size of three was too small for statistical analysis, two of the children (Arg622Trp and Arg1200Trp) had composite scores in the “average” range, whereas the third (Arg1200Trp) had a “very high” composite score.…”
Section: Discussionsupporting
confidence: 93%
“…TSC2 pathogenic variants included frameshift (28%), nonsense (23%), missense (23%), splice site (14%), and deletion (12%). Three of the patients had TSC2 missense variants (Arg622Trp and Arg1200Trp) that had been previously associated with a milder phenotype 23,24 and unless otherwise specified, were included in the TSC2 group in analyses. There were no significant differences in sex, ethnicity, gestational age, and paternal age between the three groups: TSC1, TSC2, and NMI (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenic c.3106T>C (p.Ser1036Pro) variant in exon 26 of TSC2 has been found in a single family with mild phenotype (brain and skin findings, normal cognitive level) and recurrent seizures in some members (O'Connor, Kwiatkowski, Roberts, Wollmann, & Huttenlocher, 2003). Recently, Farach et al (2017) found that the c.1864C>T (p. which can be summarized as milder than those with TSC2 pathogenic variants and similar but more severe with respect to renal findings than those with a TSC1 pathogenic variant (Camposano, Greenberg, Kwiatkowski, & Thiele, 2009;Peron et al, 2018). The only caveat to this general statement is that some NMI individuals with a severe clinical presentation have been reported.…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%
“…The pathogenic c.3106T>C (p.Ser1036Pro) variant in exon 26 of TSC2 has been found in a single family with mild phenotype (brain and skin findings, normal cognitive level) and recurrent seizures in some members (O'Connor, Kwiatkowski, Roberts, Wollmann, & Huttenlocher, 2003). Recently, Farach et al (2017) found that the c.1864C>T (p.…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%